Be a great boss one year to success - Hakala-Ausperk, Catherine (ALA guides for the busy librarian, 2011)
Moving into a library management position can feel like a daunting and solitary pursuit. Graduate school courses in management are expensive and often hard to find, and even having a mentor at hand is no guarantee of a successful transition. To help library managers improve their skills and acumen, renowned speaker and trainer Hakala-Ausperk presents a handy self-study guide to the dynamic role of being a boss.